Research of electrophysical properties of solar elements by impedance spectroscopy method using a specially designed low temperature microcryogenic measuring cell - Aimaganbetov, K.P.; Shegebay, S.K.; Aldiyarov, A.U.; Zhantuarov, S.R.; Tokmoldin, N.S. (Recent Contributions to Physics, 2021)
The paper presents studies of two types of solar cells: silicon heterojunction and perovskite. The investigations were carried out by the method of impedance spectroscopy in the frequency range from 100 Hz to 5 MHz at a rather wide temperature range from 128 to 299 K. Measurements at this temperature range were carried out using a specially designed microcryogenic cell. The basic structure of a microcryogenic cell is also described in detail in this work. The cell is capable of operating in the range from 16 K to room temperature and is equipped with three contacts, which makes it possible to study the electrophysical properties of both flat and bulk samples. In the course of the studies carried out, data were obtained on the dark active and reactive resistances, as well as Nyquist curves at the above different temperatures. The results obtained demonstrate the clear influence of environmental factors, such as the temperature of the ambient samples, on the measurements of the electrophysical characteristics of solar cells, the studies of which are relevant today. Thus, the electrophysical properties of samples promising in renewable energy have been studied using a specialized method for studying semiconductor devices (impedance spectroscopy) and a measuring device of its own assembly and design, which makes it possible to supplement research by varying and creating low temperatures surrounding the samples. Keywords: photovoltaics, semiconductors, solar cells, impedance spectroscopy, low temperature measurements, Nyquist curves